(untitled) (Journal of the College of Basic Education, 2022)
Legal translation is often treated as a specific category in its own right within non-literary translation and is described as “the ultimate linguistic challenge,” combining the inventiveness of literary translation with the terminological precision of the technical translation. Nonetheless, the primary purpose of legal translation is to recreate the SL content in the TL in such a manner as to achieve the identical meaning, intent and legal effect. Each country has its own legal terminology (based on the particular legal system of that country), which will often be quite different even from the legal terminology of another country with the same language, so, unlike scientific or other technical terminology, legal translation is often more difficult than other types of technical translation because of the system-bound nature of legal terminology. When it comes to legal translation, a translator is required to have an extensive knowledge of law and to understand local cultures and sociological nuances of those cultures in order to convey the message across sufficiently